2016
DOI: 10.1021/acs.analchem.6b03551
|View full text |Cite
|
Sign up to set email alerts
|

Detection and Mapping of Cannabinoids in Single Hair Samples through Rapid Derivatization and Matrix-Assisted Laser Desorption Ionization Mass Spectrometry

Abstract: The sample preparation method reported in this work has permitted for the first time the application of matrix-assisted laser desorption ionization mass spectrometry (MALDI-MS) profiling and imaging for the detection and mapping of cannabinoids in a single hair sample. MALDI-MS imaging analysis of hair samples has recently been suggested as an alternative technique to traditional methods of GC/MS and LC/MS due to simpler sample preparation, the ability to detect a narrower time frame of drug use, and a reducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
62
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(62 citation statements)
references
References 44 publications
0
62
0
Order By: Relevance
“…These standards could be included as early in the workflow as dosing the animals/cells up to right before the ions enter the instrument. 2,28,29 For MALDI, the standards are typically applied prior to matrix application using the same automatic sprayer systems described below. 3032 Chumbley et al has done a comprehensive study to determine the proper inclusion of the standard (e.g., with matrix, under the tissue section, or sandwiching the section with matrix), and it was found that depositing the standards followed by matrix to be optimal for MSI mapping of spatial distribution of the drug rifampicin.…”
Section: Sample Preparationmentioning
confidence: 99%
See 3 more Smart Citations
“…These standards could be included as early in the workflow as dosing the animals/cells up to right before the ions enter the instrument. 2,28,29 For MALDI, the standards are typically applied prior to matrix application using the same automatic sprayer systems described below. 3032 Chumbley et al has done a comprehensive study to determine the proper inclusion of the standard (e.g., with matrix, under the tissue section, or sandwiching the section with matrix), and it was found that depositing the standards followed by matrix to be optimal for MSI mapping of spatial distribution of the drug rifampicin.…”
Section: Sample Preparationmentioning
confidence: 99%
“…31,53 Other steroids (e.g., tetrahydrocannabinal) have also been targeted using 2-fluoro-1-methylpyridinium p -tolunesolfonate as a derivatization agent. 29 N-glycans (Figure 2), fatty acids, and neurotransmitters have all been targets through other, unique on-tissue assays. 28,42,52 Compared to the traditional spraying of reagent, which usually produces poor spatial resolutions (>100 µ m), electrospray deposition has been successfully utilized to derivatize fatty acids while achieving a high spatial resolution (20 µ m).…”
Section: Sample Preparationmentioning
confidence: 99%
See 2 more Smart Citations
“…The analysis of a very short segment, in the submillimeter range, from a single hair strand is now possible with modern analyzers. Sensitive methods involving gas chromatography/tandem mass spectrometry, LC/MS/MS, and MALDI mass spectrometric imaging have been described for single-strand hair drug analysis (10)(11)(12). MALDI mass spectrometric imaging requires less sample preparation but is less sensitive than LC/MS/MS.…”
Section: Uttam Garg*mentioning
confidence: 99%